2019
DOI: 10.1111/febs.15070
|View full text |Cite
|
Sign up to set email alerts
|

P38α MAPK coordinates the activities of several metabolic pathways that together induce atrophy of denervated muscles

Abstract: Physiological or pathological muscle disuse/inactivity or loss of the neural‐muscular junction cause muscle atrophy. Atrophy‐inducing conditions cause metabolic oxidative stress in the muscle tissue, activation of the ubiquitin‐proteasome and of the autophagosome‐lysosome systems, enhanced removal of the damaged proteins and organelles, and loss of muscle mass and strength. The signaling pathways that control these catabolic processes are only partially known. In this study, we systematically analyzed the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…It is believed that protein synthesis and degradation in muscle are regulated by signaling transduction related to oxidative stress, autophagosome-lysosome systems, hormones, and so on ( 43 ). Mitochondria are the aerobic energy production site, and ROS as by-product of mitochondrial metabolism may cause mtDNA mutations and dysfunction, destroy antioxidant defensing system, and cause damage to tissues ( 28 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that protein synthesis and degradation in muscle are regulated by signaling transduction related to oxidative stress, autophagosome-lysosome systems, hormones, and so on ( 43 ). Mitochondria are the aerobic energy production site, and ROS as by-product of mitochondrial metabolism may cause mtDNA mutations and dysfunction, destroy antioxidant defensing system, and cause damage to tissues ( 28 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that autophagy deficiency plays a role in various forms of hereditary muscular dystrophy, including Bessler myopathy, Ullrich congenital muscular dystrophy, and Duchenne muscular dystrophy (DMD) [37]. More recently, Odeh and collaborators demonstrated that autophagy flux was slowed down or even blocked in denervated muscles [38]. Moreover, it has been reported that a correct autophagy flux is fundamental for myofiber survival [39,40] and satellite cells stemness [41].…”
Section: Discussionmentioning
confidence: 97%
“…Under these conditions, p38 MAPK upregulates E3 ligases like MAFbx/Atrogin1 and Murf1 targeting proteins for proteasome degradation [ 97 , 98 , 99 , 100 , 101 ]. Inhibition of p38 MAPK activity protects muscle from the oxidative damage and prevents proteolysis, and was, therefore, suggested as a potential target for the treatment of muscle atrophy [ 102 , 103 , 104 ]. The continuous activity of p38 MAPK is also involved in the etiology of inflammatory diseases and specifically bowel diseases, like ulcerative colitis and Crohn’s disease [ 105 ].…”
Section: P38 Mapk In the Development Of Insulin Resistance And Typmentioning
confidence: 99%
“…However, as mentioned before, since p38 MAPK activity is vital for mitochondrial function and oxidative metabolism, its inhibition may have adverse effects on muscle glucose metabolism [ 8 , 56 , 62 ]. Inhibition of p38 MAPK is anticipated to reduce skeletal muscle oxidative phosphorylation and compensate for the lost energy by increasing anaerobic glycolysis [ 102 ]. The prevailing model is that excessive calorie intake cause mitochondrial electron leak, accumulation of ROS, mitochondrial dysfunction, and insulin resistance [ 68 , 107 , 108 ].…”
Section: P38 Mapk In the Development Of Insulin Resistance And Typmentioning
confidence: 99%